ENHANCING FOOD SAFETY AND HALAL REGULATORY AWARENESS THROUGH IN-HOUSE TRAINING AT POLITEKNIK ATK - Ratri Retno Utami; Diana Ross Arief; Rofiatun Nafiah; Atiqa Rahmawati; Naimah Putri (Jurnal Agro Dedikasi Masyarakat (JADM), 2026)
The increasing awareness of food safety and halal product status has become a critical issue in the food industry, particularly following the implementation of mandatory halal certification in Indonesia. The Halal Center of Politeknik ATK has been designated as a Halal Product Process Assistance Agency (LP3H), responsible for assisting micro and small enterprises (MSEs) in the halal certification process through the self-declare scheme. However, limited understanding of food safety principles and halal regulations among halal advisors remains a key challenge, potentially hindering certification processes. This study aims to enhance participants’ understanding of food safety principles and halal regulatory requirements through an in-house training program. The training was delivered using lectures, interactive discussions, and case studies, involving 20 participants consisting of halal advisors and prospective advisors from academic staff and the general public.A mixed-method evaluation was conducted using pre-tests, post-tests, and questionnaires. The results showed an increase in the average score from 83.5 in the pre-test to 93.68 in the post-test, indicating improved participant understanding. Participants also reported high satisfaction with the quality of the materials, instructor competence, and overall training implementation. These findings indicate that training on food safety and halal regulations is an effective strategy for enhancing knowledge and awareness, thereby supporting the implementation of halal product assurance and certification in Indonesia